221k views
1 vote
HELPPPPPPPP why is the answer D?

HELPPPPPPPP why is the answer D?-example-1
User Ericj
by
5.7k points

2 Answers

4 votes
We can solve for x by raising both sides to the -3 power (which is the reciprocal of -1/3):

(c^-1/3)^-3 = x^-3
c^1=x^-3
c=x^-3

Since the exponent on the x is a negative, we have to move it to the denominator to make it positive:

c= 1/x³
User NJMR
by
5.7k points
1 vote
I can hardly see the minus sign in front of the (1/3). Is it (c^ - 1/3)? If it is, then the relationship is 1/c^(1/3) = x

This is where it gets very convoluted. What I have written at the end of the first paragraph indicates an inverse relationship. As x goes up in value, c becomes smaller. To get c back in the numerator, the easiest way to do it is take the reciprocal of both sides.

What you get is c^1/3 = 1/x Now you can cube both sides.

c^(1/3)^3 = (1/x)^3
c^1 = 1^3 / x^3
c = 1 / x^3

D <<<<< answer. But that minus sign better be there.
User Brian Yencho
by
5.7k points